New Quasi-Atomic Nanoheterostructures: Superatoms and Excitonic Quasi-Molecules - Pokutnyi, S.I.; Gorbyk, P.P.; Salejda, W.; Persano Adorno, D.; Khasanov, O.K.; Fedotova, O.M. (Наносистеми, наноматеріали, нанотехнології, 2016)
In this review, the state-of-the-art of research of artificial atoms (superatoms or quasi-atomic nanoheterostructures) and more complex nanostructures based on them—synthetic molecules is discussed, a new model of an artificial atom, which satisfactorily explains its electronic properties, is proposed, and the prospects for development of the new scientific trend are mentioned.